2012
DOI: 10.1016/j.neulet.2011.10.045
|View full text |Cite
|
Sign up to set email alerts
|

Addition of NMDA-receptor antagonist MK801 during oxygen/glucose deprivation moderately attenuates the upregulation of glucose uptake after subsequent reoxygenation in brain endothelial cells

Abstract: During stroke the blood-brain barrier (BBB) is damaged which can result in vasogenic brain edema and inflammation. The reduced blood supply leads to decreased delivery of oxygen and glucose to affected areas of the brain. Oxygen and glucose deprivation (OGD) can cause upregulation of glucose uptake of brain endothelial cells. In this letter, we investigated the influence of MK801, a non-competitive inhibitor of the NMDA-receptor, on the regulation of the glucose uptake and of the main glucose transporters glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Many drugs show the neuroprotective effects such as NMDA receptor antagonist, calcium antagonists and histone deacetylases (HDACs) [18][19][20]. Nowadays, pharmacodynamic constituents from natural medicines have been regarded as the focus in pharmaceutical development.…”
Section: Discussionmentioning
confidence: 99%
“…Many drugs show the neuroprotective effects such as NMDA receptor antagonist, calcium antagonists and histone deacetylases (HDACs) [18][19][20]. Nowadays, pharmacodynamic constituents from natural medicines have been regarded as the focus in pharmaceutical development.…”
Section: Discussionmentioning
confidence: 99%
“…Using cEND and cerebEND we have demonstrated that these cells respond to glucocorticoid-4,6-9 and estrogen-treatment 10 as well as to pro-infammatory mediators, such as TNFalpha 5,8 . Moreover, we have studied the pathology of multiple sclerosis 11 and hypoxia 12,13 on the EC-level. The cEND and cerebEND lines can be considered as a good tool for studying the structure and function of the BBB, cellular responses of ECs to different stimuli or interaction of the EC with lymphocytes or cancer cells.…”
mentioning
confidence: 99%
“…OGD led to the disruption of the BBB function, which could be reconstituted after combined treatment with GC and proteasome inhibitor bortezomib 12 . OGD conditions led to a strong increase in glucose uptake and in the expression of glucose transporters in cerebEND, which could be attenuated by the addition of MK801, a non-competitive inhibitor of the NMDA-receptor 13 . After reaching confluence, the cells were maintained in medium containing 2% FCS.…”
mentioning
confidence: 99%
“…Cells were maintained in an incubator at 37°C, 95% humidity and a 5% CO2/95% air atmosphere and subcultivated 1:3 or 1:20, respectively, once a week (Neuhaus et al, 2012a). Transwell experiments were accomplished as recently reported (Neuhaus et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Used FAM-labeled probes from Taqman ® (Applied Biosystems) were listed in Supplementary Table S1. In case of PPARα and LRP1, cDNA was preamplified using Taqman PreAmp Master mix (2x) prior qPCR analysis according to Neuhaus et al (2012a, Supplementary Part). Each sample was analyzed as triplicate.…”
Section: Methodsmentioning
confidence: 99%